Antioxidant Activities and Potential Wound Healing Effects of Meniran (Phyllanthus niruri) Extract Gel - Arif, Julio; Nasution, Ali Napiah; Nasution, Sri Wahyuni; Widowati, Wahyu; Dewi, Nindia Salsabila Mia; Kusuma, Hanna Sari Widya (Folia Medica Indonesiana, 2024)
Highlights: 1. This study analyzed the potential of Meniran extract gel for wound healing therapy, a plant-based medicine that has not been thoroughly researched in the context of promoting a healthy lifestyle. 2. The analysis found that Meniran extract gel has antioxidant properties that can be used for wound treatment to improve human health. Abstract Research on the use of medicinal plants to treat numerous diseases has been widely conducted. However, for chronic wound healing, the availability of medicinal plants for treatment remains rare. Gels containing active plant-based compounds may provide a solution. Phyllanthus niruri, known as "meniran" in Indonesian, is a medicinal plant used traditionally to cure various diseases. This study aimed to examine the antioxidant activities of Meniran extract gel, potentially for wound healing. Meniran was extracted using 70% methanol and formulated into a gel. The Meniran gel was composed of three formulations: 3%, 4%, and 5% sodium carboxymethylcellulose (CMC-Na) supplemented with 5% Meniran extract. The quality of the gel was assessed based on homogeneity, spreadability, pH, and viscosity. This study utilized 2,2"²-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays to evaluate the antioxidant activity of Meniran gel at seven different concentrations through its scavenging capacities. The results were calculated to determine the median inhibitory concentration (IC50). Analysis of variance (ANOVA) and post-hoc Tukey's honestly significant difference (HSD) were used for statistical analysis (p < 0.05). The three Meniran gel formulations showed good quality with spreadability ranging from 5.37 to 5.59 cm, pH levels from 5.90 to 6.03, and viscosity from 9.080 to 9.230 cps. Higher gel concentrations led to an increase in the free radical DPPH- and ABTS-scavenging activities. The highest DPPH and ABTS assays were found at 1,000 Î¼g/mL with IC50 values of 69.72 Î¼g/mL and 20.15 Î¼g/mL, respectively. In conclusion, Meniran gel formulas exhibit good standards and have antioxidant properties suitable for wound healing therapy.